1976
DOI: 10.1152/jappl.1976.41.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas physical properties and flow on lower pulmonary resistance

Abstract: We measured lower pulmonary resistance (Rlp) in eight dogs and three men breathing gas mixtures having different densities (p) and similar viscosities (mu). Rlp increased with gas density and with flow rate (V). In the dogs, these effects were not observed in lung segments subtended from 4-mm-ID bronchi; in more central airways, resistance varied approximately as (mup V)0.5. These results are compatible with Poiseuille flow in peripheral airways, and, in central airways, with flow resistance described by the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 0 publications
0
24
2
Order By: Relevance
“…The partial pressure of O 2 in the alveolus is further affected by the partial pressure of CO 2 in the pulmonary capillary blood. 7,8 Ventilation and perfusion are further influenced by variation in distribution of ventilation and perfusion. The major determinants of distribution of pulmonary blood flow include cardiac output, pulmonary artery pressure, gravity, posture, and interaction of pulmonary artery pressure with airway pressure and pulmonary venous pressure.…”
Section: Physiology Of the Respiratory Systemmentioning
confidence: 99%
“…The partial pressure of O 2 in the alveolus is further affected by the partial pressure of CO 2 in the pulmonary capillary blood. 7,8 Ventilation and perfusion are further influenced by variation in distribution of ventilation and perfusion. The major determinants of distribution of pulmonary blood flow include cardiac output, pulmonary artery pressure, gravity, posture, and interaction of pulmonary artery pressure with airway pressure and pulmonary venous pressure.…”
Section: Physiology Of the Respiratory Systemmentioning
confidence: 99%
“…Alteration of inhaled gas density by changing gas composition or ambient pressure has been a useful means to exper imentally alter lung mechanics [3,[10][11][12][13][14], Increasing gas density will increase airway resistance in the downstream segment and probably the upstream segment as well at lung volumes greater than 25% of vital ca pacity [12][13][14], As a result both inspiratory and expiratory flows are decreased [10,11,14], work of breathing and oxygen con sumption are increased [11], and exercise performance can be impaired and asso ciated with alveolar hypoventilation [13], Indeed, normal subjects breathing dense gas, especially at high levels of ventilation, behave mechanically like patients with diffuse obstructive lung disease [22], Thus, the use of dense gas to induce airways ob struction should provide a more realistic model of obstructive lung disease than using a fixed external flow resistance. Breathing gas of decreased density, by de creasing respiratory impedance, has the opposite effect on lung mechanics and ventilatory behavior [3,15,16], Utilizing different gas densities to study hyperoxic hypercapnia, the SF6 mixture was more than three times denser than that of the control (N2) gas, while the He mix ture was half as dense (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Results of the various studies aimed at describing airway flow conditions have shown that the latter are turbulent in the larynx and trachea, even during resting breathing, and become laminar as the proximal conducting airways are reached (13,14,16,17). The transition between turbulent and laminar flow occurs between the first and second generation of bronchi (main stem and lobar) during quiet breathing (flow rate of 0.5 l/s) (13).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Basically, the relationship between driving pressure (DP) and flow (V ) takes into account viscosity (l) and density (q) and can be described by the following equations, depending on the nature of flow (16) (Fig. 2):…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation